Oscillation Properties for Second-Order Partial Differential Equations with Damping and Functional Arguments - Run Xu; Yuhua Lu; Fanwei Meng (Abstract and Applied Analysis)
Using an integral averaging method and generalized Riccati technique, by introducing a parameter β≥1, we derive new oscillation criteria for second-order partial differential equations with damping. The results are of high degree of generality and sharper than most known ones.